PENGARUH VARIASI GAYA BELAJAR TERHADAP PRESTASI AKADEMIK SISWA KELAS 5 DI SD IT AL HANIF CILEGON - Syafana Nur Arfiah; Desty Endrawati Subroto; Lusi Yana Juliyanti; Lutpiani Nurul Amanah; Nurwahyuwana Nurwahyuwana; Muhamad Ilham Aristama (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to analyze the influence of learning style variations on the academic achievement of fifth-grade students at SD IT Al Hanif Cilegon. The research employs a qualitative approach using a case study method. Data collection techniques include participatory observation, in-depth interviews, and document analysis. The study sample consists of 28 students, comprising 13 boys and 15 girls, selected through purposive sampling. Data analysis follows the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing. The findings reveal three primary learning styles that affect students' academic performance: visual, auditory, and kinesthetic. Visual learners tend to comprehend material more effectively through images, diagrams, and other visual media, while auditory learners absorb information more easily through verbal explanations and discussions. Kinesthetic learners, on the other hand, demonstrate a better understanding through physical activities and hands-on experiences. Additionally, learning environment factors, the role of teachers in facilitating appropriate teaching methods, and parental involvement significantly contribute to students' academic success. The study implies the importance of implementing diverse and adaptive teaching methods tailored to students' learning styles to optimize their academic potential. By understanding students' learning style characteristics, teachers can create more effective and inclusive learning experiences.